UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - Y.a, Rosalina; Wiryaningtyas, Dwi Perwitasari; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Financial management is all company activities related to efforts to obtain the necessary funding with minimal costs and the most favorable terms, as well as efforts to use these funds as efficiently as possible. assets, log size, stock market value, etc. The value of the company is the selling price of the goods when the goods are sold. The capital structure is an illustration of the form of the company's financial proportions, namely between owned capital which is sourced from long-term liabilities and shareholder's equity which is a source of financing for a company. To find out the size of the company on the capital structure with firm value as an intervening variable in food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2020 period. In this study, the sample was taken using purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). Firm size has a significant positive effect on capital structure. Firm size has a significant positive effect on firm value. Capital structure has a significant negative effect on firm value. Accepted Firm size has a significant negative effect on firm value through capital structure.